Bread for health-improving - Semenova, Anastasia; Mykhonik, Larysa; Hryshchenko, Anna; Drobot, Vira (My University, 2013)
Adding flakes enriches bread with dietary fibers, minerals and vitamins. And the presence of DWG allows increasing the amount of groats in the products without impairing their quality, increasing the protein value to a great extent, reducing the amount of easily digestible carbohydrates and lowering glycemic index of bread.
Keywords: protein-cereal bread; cereal; buckwheat flakes; dry wheat gluten; білково-круп’яний хліб; вівсяні пластівці; гречані пластівці; суха пшенична клейковина; белково-крупяной хлеб; гречневые хлопья; сухая пшеничная клейковина; кафедра технології хлібопекарських і кондитерських виробів